Drug Delivery: Breaching the Hyaluronan Barrier with PH20‐Fc Facilitates Intratumoral Permeation and Enhances Antitumor Efficiency: A Comparative Investigation of Typical Therapeutic Agents in Different Nanoscales (Adv. Healthcare Mater. 22/2016). Issue 22 (November 2016) - Liu, Shan; Wei, Wei; Xie, Bo; Yue, Hua; Ni, Dezhi; Bao, Yali; Ma, Guanghui; Su, Zhiguo G.
Abstract : On page 2872, Guanghui Ma, Zhiguo Su, and co‐workers construct a long‐acting hyaluronidase (PH20‐Fc) as a diffusion facilitator for typical anticancer agents: doxorubicin, trastuzumab, and gold nanorod. Although effective, the performances vary among these therapeutic agents. Trastuzumab benefits most from PH20‐Fc with a best improvement in penetration and accumulation. Their systematic investigations thus reveal the importance of therapeutics size effect when using diffusion facilitator for anticancer therapy.